Production Techniques of Fission Molybdenum-99 via Highly Enriched Uranium: A review - HE Yao;LIU Fei;ZHANG Rui (Journal of Isotopes, 2020)
The demand of the isotope molybdenum-99 (99Mo) exploded since its daughter isotope—the Technetium-99m (99mTc), has been the most widely used medical radioisotope all over the world, accounting for >80% of total nuclear diagnostics worldwide. In this review, discusses are focused on radiochemical routes for the production of 99Mo, (including target materials, separation, purification) and the historical viewpoint of 99Mo technology developments.